BARRIERS ON DIABETES MANAGEMENT ADHERENCE IN CHILDREN WITH TYPE 1 DIABETES MELLITUS: A LITERATURE REVIEW - Fatkuriyah, Lailil; Nafista, Ulfia Fitriani (Journal of Nursing Periodic, 2025)
Abstract Introduction: Managing diabetes is complex and demands daily responsibilities like regular blood glucose testing, intensive insulin treatment, careful dietary monitoring, and enhanced physical activity. These challenges make it difficult for children and their families to maintain consistent adherence to diabetes management routines. Failure to adhere to diabetes management can lead to serious complications and may even result in death. Identifying the factors that hinder treatment adherence is essential for developing effective strategies and interventions to overcome these obstacles and improve diabetes management in children. This study aimed to identify barriers on diabetes management adherence in children with Type 1 Diabetes Mellitus. Methods: The research design used a systematic review following the PRISMA guidelines and utilized five databases including Proquest, Science Direct, Springer Link, Sage Journals, and Google Scholar with the keywords: “Barriers” OR “Challenges” OR “Difficulties” AND “Diabetes management” AND “Adherence” AND “Children” AND “Type 1 Diabetes Mellitus”. A total of eight articles were reviewed based on the inclusion criteria. The JBI Critical Appraisal Tools were also used as a guideline to evaluate the quality of the articles. Results: This review identifies various barriers to adherence in diabetes management in children with T1DM, including personal, sociocultural, interpersonal, environmental, and financial barriers. Conclusions: The findings from this review suggest several strategies to address barriers to diabetes management adherence involving parents, family, school, and health services. Keywords: Barriers, diabetes management, children, type 1 diabetes mellitus